2020
DOI: 10.17516/1999-494x-0249
|View full text |Cite
|
Sign up to set email alerts
|

3D Simulation of Gas Flow into the Formula Student Car Intake System

Abstract: Formula Student Car (FS) is an international race car design competition for students at universities of applied sciences and technical universities. The winning team is not the one that produces the fastest racing car, but the group that achieves the highest overall score in design, racing performance. The arrangement of internal components for example, predicting aerodynamics of the air intake system is crucial to optimizing car performance as speed changes. The air intake system consists of an inlet nozzle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…This rate has been calculated as 33.28% in absorbed sound decibels. In a similar study conducted by Mohamed et.al in the literature, it was observed that the acoustic pressure decreased by 10% in the model designed by increasing the number of holes in the exhaust muffler [32]. It can be said that this value is like the results obtained in this study.…”
Section: Discussionsupporting
confidence: 88%
“…This rate has been calculated as 33.28% in absorbed sound decibels. In a similar study conducted by Mohamed et.al in the literature, it was observed that the acoustic pressure decreased by 10% in the model designed by increasing the number of holes in the exhaust muffler [32]. It can be said that this value is like the results obtained in this study.…”
Section: Discussionsupporting
confidence: 88%